Penyelesaian Pembayaran Kredit Di Bank Akibat Meninggalnya Penerima Kredit - Ferdy Waas; Adonia Ivonne Laturette; Nancy Silvana Haliwela (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2024)
In the Ambon District Court Decision, Number 84/Pdt.G/2019/PN.Amb, where the debtor on behalf of Alice de Fretes entered into an agreement credit with PT Bank Mandiri Ambon branch with collateral, namely 4 Certificates of Ownership, but over time the debtor did not make payments due to the debtor's death. Therefore, the Bank gave a warning to the heirs to continue paying the debtor's property, but they did not respond well. This writing aims to find out and explain credit settlements at banks due to the death of debtors. This paper uses a research method that is normative, namely research that is focused on providing a systematic explanation that regulates a particular category. The approach to the problem is the statute opproach and the conceptual approach and case approach. The collection of legal materials through primary legal materials is then linked to secondary legal materials. Management and analysis of legal materials is described qualitatively with the aim of describing the findings in the field. The results obtained form this writing are. Credit settlement at banks due to the death of the debtor is though consumer complaints or alternative Indonesia banking dispute resolution institutions. If the two options clearly fail to reconcile creditor dan debotrs, the dispute will be resolved through a simple lawsuit mechanism as a las resor or through litigation.